Biodiversity of fish species of Arut-Kumai Peat Waters, West Kotawaringin District, Central Kalimantan - Eddy Santoso; Gema Wahyudewantoro (Jurnal Iktiologi Indonesia, 2019)
The peat waters area such as swamps, lakes and rivers, are essential habitat for many fish which consumed by Arut-Kumai residents who live in the city of Pangkalan Bun. Fish species diversity and its potential are not yet widely known, therefore it needs to be revealed. The research aims to reveal fish biodiversity and its potential in the peat waters of the Arut Lamandau-Kumai River Basin, west Kotawaringin Regency. The study was conducted in October-December 2017. Fish samples were captured by using cast net, gill nets, hooks and rods, fish traps. During the study period, a number of 95 fish species belonging to 50 genera, 23 families dan 6 orders were collected. The most common family was Cyprinidae, followed by Siluridae, Osphronemidae, Chanidae dan Bagridae. Dominant genera were Osteochilus and Rasbora, Kyrptopterus, Betta Channa. As many as 70 species as consumption fish, 53 species as ornamental fish, while 56 species have the potential as aquaculture fish. The fish habitat in the Arut-Lamandau river is a peat area that stretches in the buffer zone of the eastern part of the Lamandau River Wildlife Reserve, that has been transformed into an oil palm plantation. In addition, logging activity is occurred mainly in peat ecosystem areas in production forest areas. These activities are thought to cause a reduction fish population in Arut-Kumai peat waters. Abstrak Kawasan perairan bergambut, berupa rawa, danau, dan sungai banyak menjadi habitat bagi ikan yang banyak dikonsumsi warga Arut-Kumai yang tinggal di kota Pangkalan Bun. Kekayaan spesies ikan dan potensi untuk pengembangan belum diketahui, sehingga perlu untuk diungkap. Penelitian bertujuan untuk mengungkap biodiversitas dan potensi spesies ikan-ikan perairan gambut di Daerah Aliran Sungai Arut Lamandau-Kumai di Kabupaten Kotawaringin Barat. Penelitian dilakukan pada Oktober-Desember 2017 dengan metode inventarisasi ikan di lokasi penelitian dengan mempergunakan jala tebar, jaring insang, kail serta joran, kotak perangkap, dan serok ikan. Ikan yang terkoleksi sebanyak 95 spesies yang mewakili 50 genera, 23 famili dan 6 ordo. Famili ikan yang paling banyak tertangkap berturut-turut adalah Cyprinidae, Siluridae, Osphronemidae, Chanidae dan Bagridae. Genus yang dominan tertangkap dari masing-masing famili ikan tersebut adalah Osteochilus dan Rasbora (Cyprinidae), Kyrptopterus (Siluridae), Betta (Osphronemidae), Channa (Chanidae). Sebanyak 70 spesies sebagai ikan berpotensi sebagai ikan konsumsi, 53 spesies sebagai ikan hias, sedangkan 56 spesies berpotensi sebagai ikan budi daya. Habitat ikan di sungai Arut-Lamandau merupakan area gambut yang terbentang di daerah penyangga bagian timur Suaka Margasatwa Sungai Lamandau yang telah berubah fungsi menjadi perkebunan sawit. Selain itu terjadi pembalakan kayu terutama wilayah ekosistem gambut di kawasan hutan produksi. Aktifitas tersebut dikhawatirkan akan menyebabkan berkurangnya populasi spesies ikan di lahan gambut Arut-Kumai.